1994
DOI: 10.1007/bf00197390
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distributions of cathepsin B and basement membrane antigens in human lung adenocarcinoma: association with invasion and metastasis

Abstract: The distributions of cathepsin B (CB) a lysosomal cysteine proteinase, type IV collagen (CIV) and laminin (LM), which are main components of basement membranes (BMs) were studied in a series of 64 human lung adenocarcinomas using an immunohistochemical technique. Over-expression of CB (> 80% positive cells) was significantly associated with the grade of tumour differentiation (p < 0.01), with lymph node metastasis (p < 0.01) and with BM degradation (p < 0.01) detected by the staining pattern of CIV and LM. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…In this study, we clearly confirmed our earlier results as we found 9.1-fold increased cath B protein concentration as well as 5.6-fold increased total cath B activity and 3.2-fold increase in the fraction of cath B activity, stable at pH 7.5 (Werle et al, 1997b) in tumour compared with normal lung tissue homogenates. Our data concerning enzyme expression revealed by IHC agree with previous investigations (Higashiyama et al, 1991(Higashiyama et al, , 1993Ozeki et al, 1993;Inoue et al, 1994;Sukoh et al, 1994aSukoh et al, , 1994b demonstrating that more elevated levels of cath B were found in primary tumours, which invaded into lymph nodes. Noteworthy, fraction of cath B activity stable at pH 7.5 (cath B A7.5 ) steadily increased in more malignant lung tumours (from pN1 to pN3).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, we clearly confirmed our earlier results as we found 9.1-fold increased cath B protein concentration as well as 5.6-fold increased total cath B activity and 3.2-fold increase in the fraction of cath B activity, stable at pH 7.5 (Werle et al, 1997b) in tumour compared with normal lung tissue homogenates. Our data concerning enzyme expression revealed by IHC agree with previous investigations (Higashiyama et al, 1991(Higashiyama et al, , 1993Ozeki et al, 1993;Inoue et al, 1994;Sukoh et al, 1994aSukoh et al, , 1994b demonstrating that more elevated levels of cath B were found in primary tumours, which invaded into lymph nodes. Noteworthy, fraction of cath B activity stable at pH 7.5 (cath B A7.5 ) steadily increased in more malignant lung tumours (from pN1 to pN3).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings agree with other univariate-and the multivariate survival analyses of cath B IHC analysis in tumour cells of adenocarcinoma (Sukoh et al, 1994a(Sukoh et al, , 1994b. Moreover, Ozeki et al (1993) further differentiated AC patients and demonstrated prognostic significance of cath B for lung AC of the Clara cell type only, but not for other subtypes of AC patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations